Factors influencing price developments of commodities - Evita Schmieg (Intereconomics, 1993)
Since developing countries are dependent to a large extent on the export of commodities, changes in commodity prices on world markets can have dramatic effects on living standards and on government budgets. The following paper examines the factors behind such changes and discusses the instruments which could be used to influence them.
Keywords: 330; Raw Materials